The relationship between physical aspects of quality of life and extreme levels of regular physical activity in adults - Erika da Silva Maciel; Roberto Vilarta; Denis Marcelo Modeneze; Jaqueline Girnos Sonati; Julia Santos Vasconcelos; Guanis Barros Vilela Junior; Marília Oetterer (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study aimed to check for any significant differences in perceived quality of life, specifically aspects of a physical nature, among volunteers who are more physically active and those less physically active in a university community. The sample consisted of 1,966 volunteers in a university community in Brazil. To assess physical activity levels, volunteers responded to the International Physical Activity Questionnaire (IPAQ), and to analyse the perception of quality of life they responded to WHOQOL-bref, which is classified into three groups according to level of physical activity, taking into account the metabolic equivalent index (MET) over a full week. For comparison, consideration was given to the first and third tertiles, respectively, namely groups of more and less active students. The results indicated that individuals who engaged in more physical activity had a more positive perception of quality of life compared to those who were less active in physical aspects related to the ability to work, energy for day-to-day activities and locomotion.